Structure and antiviral activity of a pectic polysaccharide from the root of Sanguisorba officinalis against enterovirus 71 in vitro/vivo - Kim, Minyeong; Kim, Seong Ryeol; Park, Jiye; Mun, Seo Hyeon; Kwak, Myounghai; Ko, Hyun Jeong; Baek, Seung Hoon (Carbohydrate Polymers, 2022)
The increasing prevalence and pandemic risk of viral diseases warrant the development of safe and effective treatments. In this study, we aimed to elucidate the structure and anti-enterovirus 71 (EV71) effects of polysaccharides isolated from the roots of Sanguisorba officinalis (SO), traditionally used for infectious diseases. The purified polysaccharide (S-a3) was a homogenous macromolecule (260.4 kDa) with a concave and porous surface. Linkage and NMR analyses confirmed that S-a3 is a polysaccharide interlinked with homogalacturonan, rhamnogalacturonan-I, 1,4-α-glucan, and arabinogalactan. S-a3 significantly inhibited cell death and viral gene expression in EV71-infected Vero cells, and alleviated EV71-induced body weight loss, death, and paralysis in the hSCARB2-transgenic mouse model. The effective dose of S-a3 was non-toxic to cells and mice. The antiviral mechanism of S-a3 was associated with the disruption of EV71 attachment to host cells. Our findings demonstrate that polysaccharides from SO can be a safe and effective treatment for EV71 infection.
Keywords: Antiviral activities; Arabinogalactan; Enterovirus 71; Glucans; In-vitro; Pectic polysaccharides; Pectin; Sanguisorba officinali; Structure activity; Viral disease; Animals; Antiviral Agents; Chlorocebus aethiops; Enterovirus; Enterovirus A, Human; Mice; Polysaccharides; Sanguisorba; Vero Cells; Virus Replication; Antiviral activity; Arabinogalactan; Enterovirus 71; Glucan; Pectin; Sanguisorba officinalis